Comparison between cortical and subcortical diaphragmatic motor stimulation by transcranial magnetic stimulation on patients with chronic obstructive pulmonary disease - Hanan Mohamed Ibrahim Elshoura; Ahmed Adel Ahmed Ghareeb Nofal; Hossam Salaheldin Labib (Egyptian Rheumatology and Rehabilitation)
Abstract Background Transcranial magnetic stimulation (TMS), a non-invasive method of electrically stimulating neurons in the cerebral cortex, can change neuronal and cortical activity locally and remotely by applying localized magnetic fields. TMS can be used to treat a variety of disorders and improve functional impairments by stimulating the motor cortex. Chronic obstructive pulmonary disease (COPD) is an invalidating disease that primarily compromises both respiratory and motor functions either during the acute or the chronic phase. In COPD, the diaphragm may contribute to respiratory decompensation This study aims to use TMS as a therapeutic tool in addition to conventional rehabilitative programs in COPD patients and assess this application using diaphragmatic ultrasonography (US) and 6-min walking test (6MWT). Result A case–control study with 60 COPD patients divided into three equal groups. The control group (group A) received the conventional rehabilitation program, group B received additional subcortical magnetic stimulation of the phrenic nerve roots in the neck, and group C received TMS of the diaphragmatic motor cortex area in addition. Before treatment, there was no significant difference between the groups in diaphragmatic US assessment (diaphragmatic thickness (DT) and diaphragmatic mobility (DM) or 6MWT (P > 0.05). After treatment, there was a significant improvement in groups A and B, while a highly significant improvement in group C. Conclusion The application of cortical or subcortical TMS to COPD patients improves diaphragmatic function and daily activities significantly. These advancements allowed TMS to be considered as a therapeutic tool in the COPD rehabilitation program.